Korelasi antara Rasio Limfosit Neutrofil dan Nilai Ambang Batas Siklus RT-PCR pada Bayi Terinfeksi Covid-19 - N. N. Tatura, Suryadi; Halim, Rifrita F. (Medical Scope Journal, 2024)
Covid-19 pandemic has been a new illness since the start of 2019 which was caused by SARS-CoV-2 coronavirus. In children, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection has been linked to a multisystem inflammatory syndrome and coronavirus disease 2019 (Covid-19). This study aimed to obtain the correlation between the neutrophil-lymphocyte ratio (NLR) and the cycling threshold (CT) value (viral load) of RT-PCR for Covid-19 in infant patients. This was a descriptive and analytical study with a cross-sectional design. Secondary data were obtained from medical records of March 2020 to February 2022 at Prof. Dr. R. D. Kandou Hospital, Manado. Subjects were all infants admitted or born during the recording period, with suspected or confirmed Covid 19, including infants with mothers whose Covid-19 antigen tests were reactive. Data of age, gender, diagnosis, outcome CT value of RT-PCR test, and NLR were retrieved, and analyzed with Pearson correlation, meanwhile comparison based on gender and outcome of care using the independent T-test. All analyses were conducted with IBM SPSS 26.0. The results showed that the correlation between CT value and NLR was -0.361 with a p-value of 0.067. In conclusion, there is no significant correlation between CT value and NLR level with weak correlation. However, CT and NLR values appeared to be inversely associated; the higher the NLR value, the lower the CT value. Keywords: infants; Covid-19; cycle threshold of RT-PCR; neutrophil-lymphocyte ratio